2019
DOI: 10.1080/1828051x.2018.1557019
|View full text |Cite
|
Sign up to set email alerts
|

Effects of protease supplementation of low protein and/or energy diets on growth performance and blood parameters in broiler chickens under heat stress condition

Abstract: The effects of feeding low dietary crude protein (CP) and/or metabolisable energy (ME) with or without supplemental protease on growth performance, carcase characteristics and physiological responses in broiler chickens were investigated under cyclic heat stress condition. A total of 350 day-old male broiler chicks were fed with one of the following seven experimental diets: (1) recommended-CP and recommended-ME (RPE, served as control); (2) recommended-CP and low-ME (RPLE); (3) recommended-CP and low-ME with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 61 publications
0
10
1
Order By: Relevance
“…Previous experiments conducted on serine protease and threonine and found there benefit on growth performance (Cowieson andRavindran 2008 Ayaşan et al 2009;Angel et al 2011;Fru-Nji et al 2011;Vieira et al 2013;Okan 2014a, 2014b;Ding et al 2016;Lin-Law et al 2019;Ndazigaruye et al 2019) and. In addition, it was reported that supplemental protease reduced nitrogen excretion (Aletor et al 2000;Bregendahl et al 2002;Canogullari et al 2009) and decreased feed costs, and consequently broiler industry's production.…”
Section: Introductionmentioning
confidence: 93%
“…Previous experiments conducted on serine protease and threonine and found there benefit on growth performance (Cowieson andRavindran 2008 Ayaşan et al 2009;Angel et al 2011;Fru-Nji et al 2011;Vieira et al 2013;Okan 2014a, 2014b;Ding et al 2016;Lin-Law et al 2019;Ndazigaruye et al 2019) and. In addition, it was reported that supplemental protease reduced nitrogen excretion (Aletor et al 2000;Bregendahl et al 2002;Canogullari et al 2009) and decreased feed costs, and consequently broiler industry's production.…”
Section: Introductionmentioning
confidence: 93%
“…So, in an effort to reduce the energy released during digestion, absorption, and metabolism of nutrients, dietary CP reductions have been proposed as a strategy to mitigate the harmful effects of HS in poultry ( Furlan et al, 2004 ). Numerous studies in broilers have tested the effects of feeding a reduced CP diet versus a standard CP diet under constant HS ( Alleman and Leclercq, 1997 ; Cheng et al, 1999 ; Faria Filho et al, 2005 ; Gonzalez-Esquerra and Leeson, 2005 ; Awad et al, 2018 ), cyclic HS ( Cheng et al, 1999 ; Liu et al, 2016 ; Awad et al, 2018 ; Zulkifli et al, 2018 ; Amiri et al, 2019 ; Lin Law et al, 2019 ; Soares et al, 2020 ) and hot climates ( Zaman et al, 2008 ; Laudadio et al, 2012 ; Awad et al, 2014 , 2015 , 2017 ; Lin Law et al, 2019 ; Attia et al, 2020 ). Table 1 summarizes 21 HS broiler trials comparing reduced CP diets (ranging from 143 to 190 g/kg CP) and standard CP diets (ranging from 183 to 223 g/kg CP), with both diets in each study formulated to meet or exceed a specific nutritional requirement, such as the Nutrient Requirements of Poultry ( NRC, 1994 ) or breeder recommendations, or to contain similar AA profiles.…”
Section: Influence Of Dietary Crude Protein Contentmentioning
confidence: 99%
“…Research has demonstrated that the addition of exogenous protease was able to modify the gut morphology, such as increasing villus length and supplementing the lack of endogenous enzyme secretion [8]. In addition, the addition of exogenous protease allows for a reduction in the amount of diet crude protein with no adverse effect on the feed intake, weight gain, and survivability rates in broilers [9].…”
Section: Introductionmentioning
confidence: 99%